The genome sequence of the Northern Deep-brown Dart, Aporophyla lueneburgensis (Freyer, 1848) - Boyes, D; Holland, PWH (F1000Research, 2023)
We present a genome assembly from an individual female Aporophyla lueneburgensis (the Northern Deep-brown Dart; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence is 978.3 megabases in span. Most of the assembly is scaffolded into 31 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 15.5 kilobases in length. Gene annotation of this assembly on Ensembl identified 12,580 protein coding genes.